JENIS TERAPI DUKUNGAN SPIRITUAL YANG MEMPENGARUHI KECEMASAN PADA PASIEN PRE OPERASI: LITERATUR REVIEW - Chatarina Hatri Istiarini; Anggreini Putri Ferdinand; Ayu Pratiwi; Donatus Newo; Dwitiya Purbo Sasongko; Ika Yuni Prihantari; Romenson Wolla (Universitas Respati Yogyakarta, 2021)
Types of Spiritual Support Therapy Affecting Anxiety in Preoperative Patients: Literature ReviewBackground: Surgery is a stressful complex event. Surgery is always preceded by certain emotional reactions by the patient. Preoperative anxiety is related to patients concerns about the disease process, hospital care, anesthesia and surgery (Lemos et al, 2019). When experiencing anxiety, stress, individuals seek support from their religious beliefs. With an increase in anxiety in preoperative patients, the authors made an Integrated Review of Literature about types of Spiritual Support Therapy that Affects Anxiety in Preoperative Patients. Objectives: To identify types of Spiritual Support Therapy that Affects Anxiety in Preoperative Patients. Methods: The research used Literature Review. The literature review begins with the identification of phenomena that often occur in the operating room, and search for articles on trusted sites related to Spiritual Support Therapy that Affects Anxiety in Preoperative Patients. Results: 8 types of Spiritual Support Therapy that Affects Anxiety in Preoperative Patients are Classical Music Therapy, Murrotal Al-Quran, Christian Religious Music, Dzikir, Prayer Guidance, Spiritual Relaxation Guidance, Spiritual Emotional Freedom Technique and Audio Visual Distraction: Islamic Studies. Conclusion: Classical Music Therapy, Murrotal Al-Quran, Christian Religious Music, Dzikir, Prayer Guidance, Spiritual relaxation guidance, SEFT and Audio Visual Distraction: Islamic studies can be used to reduce anxiety in preoperative patients.